Ageing of the population - a time for action : the role of public health. - ELDEMIRE, D. (1995)
Notes that the changing age composition of the population has policy implications with regard to the provision of health and social services. Advises that an effective health service for older persons will need to be promotive, preventive, curative and rehabilitative. Stresses that elderly persons are particularly subject to chronic diseases and disabilities, and are therefore in need of continuity of health care. Greater emphasis will therefore have to be placed on public health care providers